2014
DOI: 10.1155/2014/717219
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chromium Picolinate Supplementation on the Pancreas and Macroangiopathy in Type II Diabetes Mellitus Rats

Abstract: Purpose. The aim was to explore the effect of the chromium picolinate (CrPic) administration on the pancreas and macroangiopathy of type II diabetes mellitus rats. Methods. The type II diabetes mellitus (T2DM) rat model was induced by low-dose streptozotocin (STZ). The rats were randomly divided into 5 groups (ten rats in each group). After supplementing CrPic for 15 weeks, the histopathological examination was performed by hematoxylin-eosin (HE) staining. Serum insulin and NO level were determined by radioimm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…The pathological results showed that the hepatocytes in the liver of the T2DM group rats were disordered, enlarged, and had deformation of vacuolated balloon; the pancreatic islets in the pancreas were sparsely distributed and vacuolated; the smooth muscle layer of the colon was thinned and the number of myocytes was reduced; the glomeruli in the kidney tissue were swollen and enlarged; the epithelial cells of the renal tubules were swollen or detached; the renal interstitium was infiltrated with inflammatory cells; and mesangial proliferation and interstitial fibrosis were also observed. The above results are consistent with the pathological manifestations of T2DM ( Huang et al., 2014 ; Fan et al., 2018 ). The intervention of PDJQ can reduce blood glucose and improve dyslipidemia, IR, and pathological changes of kidney, liver, pancreas, and colon tissues in T2DM rats.…”
Section: Discussionsupporting
confidence: 90%
“…The pathological results showed that the hepatocytes in the liver of the T2DM group rats were disordered, enlarged, and had deformation of vacuolated balloon; the pancreatic islets in the pancreas were sparsely distributed and vacuolated; the smooth muscle layer of the colon was thinned and the number of myocytes was reduced; the glomeruli in the kidney tissue were swollen and enlarged; the epithelial cells of the renal tubules were swollen or detached; the renal interstitium was infiltrated with inflammatory cells; and mesangial proliferation and interstitial fibrosis were also observed. The above results are consistent with the pathological manifestations of T2DM ( Huang et al., 2014 ; Fan et al., 2018 ). The intervention of PDJQ can reduce blood glucose and improve dyslipidemia, IR, and pathological changes of kidney, liver, pancreas, and colon tissues in T2DM rats.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that Cr can improve glycometabolism and lipid metabolism in diabetes mellitus [ 29 31 ], due to its role in glucose/insulin metabolism [ 32 ]. Previous studies also indicated that Cr could affect lipid metabolism and reduce body fat deposition of broilers [ 18 , 28 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Mahmoud et al (13), it was observed that type 2 diabetic rats exhibited a signifi cantly elevated fasting blood glucose and HOMA-IR, accompanied with diminished serum insulin levels, and insulin resistance has developed in these animals (13). Huang et al (14) reported that HbA1c (%) levels, the indicator of diabetes, were signifi cantly increased in type 2 diabetes mellitus rats (14). Estimation of HbA1c% has been found to be particularly useful in monitoring the effectiveness of therapy in diabetes (15).…”
Section: Discussionmentioning
confidence: 99%